Factors Affecting Yemeni Women’s Use of Mobile Money Technology (The International Journal for Scientific Research, 2024)
The study aimed to investigate the factors affecting Yemeni women's use of mobile money technology, through a set of variables derived from the unified theory of acceptance and use of technology.A descriptive analytical approach was used, and a questionnaire was designed to collect data from a sample of (401) of Yemeni women users and non-users of mobile money technology. The data was analyzed using simple, multiple, stepwise regression and structural modeling to test the study model.The results showed that the factors (innovation adoption, perceived enjoyment of Try and use, social influence, financial and technological knowledge, ease of use, trust and privacy, compatibility, perceived usefulness) collectively explained 78% of the variance in the dependent variable represented by (Yemeni women's use of mobile money technology). It also showed a positive statistically significant impact of the independent variables (compatibility, perceived enjoyment of Try and use, perceived usefulness, trust and privacy) on Yemeni women's use of mobile money technology. While the impact of the factors (innovation adoption, social influence, financial and technological knowledge, ease of use) was statistically insignificant.The study recommended the need for financial and technological awareness for Yemeni women and highlighting the importance of their use of mobile money technology and spreading awareness of its benefits to increase women's usage rates.
Keywords: Mobile Money Technology; Yemeni Women; The Unified Theory of Acceptance and Use of Technology